Fast trajectory planning by design of initial trajectory in overhead traveling crane with considering obstacle avoidance and load vibration suppression. (September 2016) - Inomata, Akira; Noda, Yoshiyuki
Abstract: This paper is concerned with an advanced transfer trajectory planning method of 2-Dimensional transfer machine with vibrational element such as an overhead traveling crane. In the 2-D transfer machine, it is required to reach the target position in a short time, avoid the obstacles, and suppress the vibration. In recent years, the authors have proposed the trajectory planning method using the optimization problem with considering input and state constraints in the transfer system, obstacle avoidance and vibration suppression. However in the previous approaches, it takes a long time to derive the reference trajectory because of many variables in the optimization. Therefore in this study, we propose the fast solution for optimizing the transfer trajectory by giving a feasible initial trajectory. And, it is discussed how to give the cost function in the trajectory optimization with reducing the fluctuating cart motion. Moreover, we discuss the practical case that the proposed approach is applied to the large transfer space. The effectiveness of the proposed transfer trajectory planning method is verified by simulations of the overhead traveling crane.